A double critical mass phenomenon in a no-flux-Dirichlet Keller-Segel system - Fuhrmann, Jan; Lankeit, Johannes; Winkler, Michael (Journal de mathématiques pures et appliquées, 2022)
Derived from a biophysical model for the motion of a crawling cell, the evolution system(⋆){ut=Δu−∇⋅(u∇v),0=Δv−kv+u, is investigated in a finite domain Ω⊂Rn, n≥2, with k≥0. Whereas a comprehensive literature is available for cases in which (⋆) describes chemotaxis-driven population dynamics and hence is accompanied by homogeneous Neumann-type boundary conditions for both components, the presently considered modeling context, besides yet requiring the flux ∂νu−u∂νv to vanish on ∂Ω, inherently involves homogeneous Dirichlet boundary conditions for the attractant v, which in the current setting corresponds to the cell's cytoskeleton being free of pressure at the boundary. This modification in the boundary setting is shown to go along with a substantial change with respect to the potential to support the emergence of singular structures: It is, inter alia, revealed that in contexts of radial solutions in balls there exist two critical mass levels, distinct from each other whenever k>0 or n≥3, that separate ranges within which (i) all solutions are global in time and remain bounded, (ii) both global bounded and exploding solutions exist, or (iii) all nontrivial solutions blow up. While critical mass phenomena distinguishing between regimes of type (i) and (ii) belong to the well-understood characteristics of (⋆) when posed under classical no-flux boundary conditions in planar domains, the discovery of a distinct secondary critical mass level related to the occurrence of (iii) seems to have no nearby precedent. In the planar case with the domain being a disk, the analytical results are supplemented with some numerical illustrations, and it is discussed how the findings can be interpreted biophysically for the situation of a cell on a flat substrate. - Résumé - Dérivé d'un modèle biophysique pour le mouvement d'une cellule rampante, le système d'évolution(⋆){ut=Δu−∇⋅(u∇v),0=Δv−kv+u, est étudiée dans un domaine fini Ω⊂Rn, n≥2, avec k≥0. Alors qu'une littérature complète est disponible pour les cas dans lesquels (⋆) décrit une dynamique de population pilotée par chimiotaxie et donc s'accompagne de conditions aux limites homogènes de type Neumann pour les deux composantes, le contexte de modélisation actuellement considéré, en plus d'exiger que le flux ∂νu−u∂νv disparaisse sur ∂Ω, implique intrinsèquement des conditions aux limites homogènes de Dirichlet pour l'attractif v, qui, dans le cas présent, correspond au cytosquelette de la cellule libre de toute pression à la frontière. Il est démontré que cette modification des conditions aux limites s'accompagne d'un changement substantiel en ce qui concerne le potentiel d'émergence de structures singulières : Il est, entre autres, révélé que dans les contextes de solutions radiales dans les boules, il existe deux niveaux de masse critique, distincts l'un de l'autre quand k>0 ou n≥3, qui séparent les plages dans lesquelles (i) toutes les solutions sont globales en temps et restent bornées, (ii) à la fois des solutions globales bornées et explosives existent, ou (iii) toutes les solutions non triviales explosent. Alors que les phénomènes de masse critique qui distinguent les régimes de type (i) et (ii) appartiennent aux caractéristiques bien comprises des régimes de type (⋆), lorsqu'ils sont posés sous des conditions limites classiques sans flux dans des domaines planaires, la découverte d'un niveau de masse critique secondaire distinct lié à l'occurrence de (iii) semble n'avoir aucun précédent proche. Dans le cas planaire où le domaine est un disque, les résultats analytiques sont complétés par quelques illustrations numériques, et nous discutons de la manière dont les résultats peuvent être interprétés biophysiquement dans le cas d'une cellule sur un substrat plat.
Available online 19 April 2022
Gesehen am 06.07.2022